Setting the clock--by nature: circadian rhythm in the fruitfly Drosophila melanogaster. - Peschel, N.; Helfrich-Förster, C. (FEBS Letters, 2011)
Nowadays humans mainly rely on external, unnatural clocks such as of cell phones and alarm clocks--driven by circuit boards and electricity. Nevertheless, our body is under the control of another timer firmly anchored in our genes. This evolutionary very old biological clock drives most of our physiology and behavior. The genes that control our internal clock are conserved among most living beings. One organism that shares this ancient clock mechanism with us humans is the fruitfly Drosophila melanogaster. Since it turned out that Drosophila is an excellent model, it is no surprise that its clock is very well and intensely investigated. In the following review we want to display an overview of the current understanding of Drosophila's circadian clock.